Tax Avoidance, Corporate Governance and Firm Value in The Digital Era - Chen Siew Yee; Noor Sharoja Sapiei; Mazni Abdullah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
In this study, we examine the link between tax avoidance and firm value and identify the moderating effect of corporate governance in this digital era. Corporate tax avoidance activities have been considered as value-enhancement activities to the companies and better quality of corporate governance would positively related to firm value. This study uses a sample of Malaysian Public Listed Companies (PLCs) which ranked the top 100 companies of good disclosure in the Malaysia-ASEAN corporate governance report 2014. It was conducted using cross-sectional data by observing a final sample of 82 PLCs at one point in time. We provide evidence from Malaysia that corporate tax avoidance behaviour would actually reduce firm value and corporate governance has moderator effect on the relationship of tax avoidance and firm value. This study offers practical insights to the government and policymakers in understanding the tax avoidance behaviour of company and it helps in forming adequate and effective taxation system in Malaysia. We also give constructive apprehension to Malaysian companies to understand the negative consequences of corporate tax avoidance when engaging in tax planning activities aggressively. Most importantly, this study added more evidence to the stream of literature that investigates the role of tax avoidance strategies, as moderated by the level of corporate governance, in determining the firm value in this era of technology.